Fabrications of High‐Performance Planar Zinc‐Ion Microbatteries by Engraved Soft Templates. Issue 12 (3rd March 2021) - Jiang, Kang; Zhou, Zeyan; Wen, Xi; Weng, Qunhong
Abstract: Miniaturized energy storage devices (MESDs) provide future solutions for powering dispersive electronics and small devices. Among them, aqueous zinc ion microbatteries (ZIMBs) are a type of promising MESDs because of their high‐capacity Zn anode, safe and green aqueous electrolytes, and good battery performances. Herein, for the first time, a simple and powerful strategy to fabricate flexible ZIMBs based on tailored soft templates is reported, which are patterned by engraving and enables to design the ZIMBs featured with arbitrary shapes and on various substrates. The assembled ZIMBs employing α‐MnS as the cathode materials and guar gum gel as the quasi‐solid‐state electrolyte exhibited very high areal specific capacity of up to 178 μAh cm −2, a notable areal energy density of 322 μWh cm −2 and power density of 710 μW cm −2 . Footprint areas of the manufactured ZIMBs as small as 40 mm 2 can be achieved. The proposed method based on the engraved soft templates provides a practical route for ZIMB and other MESD designs, which is critical for portable and wearable electronics development. Abstract : Engraving soft template is a simple and powerful strategy for fabrications of zinc ion microbatteries featured with various shapes on different substrates, which not only exhibit excellent battery performances, but also show good flexibility and scalability for practical applications. This method holds great potential in development of miniaturized energy storage devices used in next‐generation wearable, flexible, and miniaturized electronics.